2021
DOI: 10.1371/journal.pone.0257161
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of equine endometrium before, during and after capsule disintegration during normal pregnancy and after oxytocin-induced luteostasis in non-pregnant mares

Abstract: The current study used RNA sequencing to determine transcriptional profiles of equine endometrium collected 14, 22, and 28 days after ovulation from pregnant mares. In addition, the transcriptomes of endometrial samples obtained 20 days after ovulation from pregnant mares, and from non-pregnant mares which displayed and failed to display extended luteal function following the administration of oxytocin, were determined and compared in order to delineate genes whose expressions depend on the presence of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In contrast, Smits et al (2018) 9 reported P19 protein downregulation in UF samples of pregnant mares compared to cyclic controls on day 13, suggesting that P19 was mostly taken up by the conceptus and not present in the UF. At transcript level, Klein et al (2021) 79 reported also a downregulation of P19 in the endometrium during pregnancy on days 14, 22, and 28. In our parallel studies, we found P19 mRNA with highest expression in GE 12 without differences between P and C and with low expression in the embryo (Rudolf Vegas et al 2021, unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Smits et al (2018) 9 reported P19 protein downregulation in UF samples of pregnant mares compared to cyclic controls on day 13, suggesting that P19 was mostly taken up by the conceptus and not present in the UF. At transcript level, Klein et al (2021) 79 reported also a downregulation of P19 in the endometrium during pregnancy on days 14, 22, and 28. In our parallel studies, we found P19 mRNA with highest expression in GE 12 without differences between P and C and with low expression in the embryo (Rudolf Vegas et al 2021, unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…The Ingenuity Pathway Analysis (IPA) software (Qiagen) was employed to identify canonical pathways and upstream regulatory elements 26 . The Z-scores were used to predict the activation state (activation or inhibition) of each upstream regulator.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies investigated the transcriptomic profile of the endometrium to gain further insight into the molecular events underlying embryo-maternal interactions during early pregnancy in mares 20 28 . The differentially expressed genes (DEGs) between pregnant and nonbred mares during early pregnancy were mainly associated with pathways related to the immune system, angiogenesis 21 , cell-to-cell interaction 26 , and prostaglandin regulation 23 . These studies advanced our understanding of the molecular pathway associated with embryo-maternal interaction in mares.…”
Section: Introductionmentioning
confidence: 99%